Innovation capabilities in EU countries: have Central and Eastern European countries been catching up? - Kondratiuk-Nierodzińska, Monika (Journal of Business Economics and Management, 2016)
The paper answers two questions: which innovation capabilities most strongly differentiate CEECs and highly developed European economies and to what extent CEECs’ performance within each of the innovation capabilities has changed over a decade. The research method is based on construction of composite indicators describing national performance within five innovation capabilities in two periods: 1998–2000 and 2010–2012 as well as regression analysis in order to test the accuracy of the main findings. The study has allowed to arrive at a conclusion that CEECs have been able to catch up to highly developed European economies with respect to absorptive capacity related to the existence and use of technological infrastructure as well as participation in inward technology transfer in the form of FDI and capital goods imports. There is, however, a lingering performance gap in new knowledge and innovation creation capabilities and R&D effort. Continuation of this trend and lack of considerable improvement also in terms of absorptive capacity related to the quality of human resources might result in CEECs’ permanent inability to catch up to their highly developed European counterparts.